2015
DOI: 10.1039/c5ee00700c
|View full text |Cite
|
Sign up to set email alerts
|

First turnover analysis of water-oxidation catalyzed by Co-oxide nanoparticles

Abstract: ARTICLE This journal isCo-oxides are promising water oxidation catalysts for artificial photosynthesis devices. Presently, several different proposals exist for how they catalyze O 2 formation from water. Knowledge about this process at molecular detail will be required for their further improvement. Here we present time-resolved 18 O-labelling isotope-ratio membrane-inlet mass spectrometry (MIMS) experiments to study the mechanism of water oxidation in Co/methylenediphosphonate (Co/M2P) oxide nanoparticles us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
50
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 84 publications
4
50
0
Order By: Relevance
“…Such exchange coupling provides a mechanism for charge localization within cubanes, as shown here, and by analogy within the metalate clusters of Co-OEC. Isotope labeling studies of oxidic cobalt OER catalysts (23,24) and computational mechanistic studies of Co-OECs (42,43), together with model studies of dicobalt complexes (23), indicate that O-O bond formation requires an adjacent Co(IV) 2 active edge site; it is necessary that two Co(IV) centers localize to the edge site of a cobaltate cluster preceding turnover, as opposed to hole equivalents delocalized over the cluster active site. As we show here, antiferromagnetic coupling provides a mechanism to drive hole localization within the cluster core.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such exchange coupling provides a mechanism for charge localization within cubanes, as shown here, and by analogy within the metalate clusters of Co-OEC. Isotope labeling studies of oxidic cobalt OER catalysts (23,24) and computational mechanistic studies of Co-OECs (42,43), together with model studies of dicobalt complexes (23), indicate that O-O bond formation requires an adjacent Co(IV) 2 active edge site; it is necessary that two Co(IV) centers localize to the edge site of a cobaltate cluster preceding turnover, as opposed to hole equivalents delocalized over the cluster active site. As we show here, antiferromagnetic coupling provides a mechanism to drive hole localization within the cluster core.…”
Section: Resultsmentioning
confidence: 99%
“…Electrochemical kinetics (19) and spectroscopic measurements (20,21) support a mechanism consisting of a minor equilibrium proton-coupled electron transfer process to generate effectively a Co(III)Co(IV) precatalyst, followed by a subsequent oxidation to generate a doubly oxidized state that drives the turnover-limiting O-O bond-forming step (22). Isotope labeling studies of active oxidic cobalt OER catalysts (23,24) establish direct coupling of oxygens on neighboring sites, thus identifying one path for O-O bond formation from a Co(IV) 2 state,…”
mentioning
confidence: 99%
“…Regarding mechanistic implications for amorphous Co oxides, the membrane-inlet mass spectroscopy (MIMS) experiments by Messinger’s group provided interesting insights of where the O—O bond formation occurs [25]. By following the time-resolved 18 O-labelling isotope-ratio with MIMS, they concluded that the O—O bond formation of the amorphous Co-oxide nanoparticles (Co/methylenediphosphonate (Co/M2P)-oxide) occurs via intermolecular oxygen-coupling between two terminal Co-OH x ligands, without the involvement of bridging oxygens.…”
Section: Operando Studies Of Oer-active Amorphous Metal Oxide Catamentioning
confidence: 99%
“…Currently, although amorphous bulk materials, such as rubber, glass, plastics, and asphalt have been exalted for many years, the in‐depth understanding of physicochemical properties and biological activities of amorphous nanomaterials (ANMs) is still critically lack because of the difficulties in preparation derived from their intrinsic metastable state . Recently, a few studies reported the extraordinary performances of ANMs, which were significantly superior to crystalline nanomaterials, such as catalytic capability and remarkable surface enhanced Raman scattering activity, which aroused great research interest in ANMs.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, although amorphous bulk materials, such as rubber, glass, plastics, and asphalt have been exalted for many years, [1][2][3] the in-depth understanding of physicochemical properties and Studies on distinctive performances and novel applications of amorphous inorganic nanomaterials are becoming attractive. Herein, Ag 2 S amorphous and crystalline nanodots (ANDs and CNDs) are prepared via facile methods.…”
Section: Introductionmentioning
confidence: 99%